1998
DOI: 10.1212/wnl.51.6.1666
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of dominant spinocerebellar and Friedreich triplet repeats among 361 ataxia families

Abstract: Pathogenic trinucleotide repeat expansions were found among 61% of the dominant kindreds. Among patients with apparently recessive or negative family histories of ataxia, 6.8% and 4.4% tested positive for a CAG expansion at one of the dominant loci, and 11.4 and 5.2% of patients with apparently recessive or sporadic forms of ataxia had FA expansions. Because of the significant implications that a dominant versus recessive inheritance pattern has for future generations, it is important to screen patients who do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
119
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(130 citation statements)
references
References 13 publications
8
119
1
Order By: Relevance
“…7 Only 38% of children/adolescents and 11% of adults with recessive ataxia have a confirmed molecular diagnosis of FRDA, and proportions are even smaller for sporadic cases, leaving ample space for genetic heterogeneity. 16,17 The recent cloning of the gene involved in ARSACS, 10 encoding a new protein of unknown function, may facilitate the diagnosis of this rare condition, by a western blot approach, as is already the case for autosomal recessive muscular dystrophies. Several genes disrupted in recessive ataxias point to a pathological mechanism involving oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…7 Only 38% of children/adolescents and 11% of adults with recessive ataxia have a confirmed molecular diagnosis of FRDA, and proportions are even smaller for sporadic cases, leaving ample space for genetic heterogeneity. 16,17 The recent cloning of the gene involved in ARSACS, 10 encoding a new protein of unknown function, may facilitate the diagnosis of this rare condition, by a western blot approach, as is already the case for autosomal recessive muscular dystrophies. Several genes disrupted in recessive ataxias point to a pathological mechanism involving oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found evidence of frequency variation between different regions in Japan. 26 Data are based on a comprehensive study in the United States by Moseley et al 27 …”
mentioning
confidence: 99%
“…Several geographically localised studies have been conducted on the prevalence of ADCAs, with the focus on the six SCA diseases. With regards to SCA3, the prevalence is at its highest in Brazil (69% of SCA cases), Portugal (58%) and China (49%) and relatively low in USA (21%), India (3%) and Italy (1%) [77,[79][80][81][82][83]. An interesting case is the founder effect of SCA7 in South Africa, where this disease represents 26.6% of SCA diseases [84], a figure that is significantly higher than the 2% occurrence worldwide [78].…”
Section: Prevalence and Incidencementioning
confidence: 99%